1985
DOI: 10.1111/j.1432-1033.1985.tb08815.x
|View full text |Cite
|
Sign up to set email alerts
|

The binding of vanadium (V) oligoanions to sarcoplasmic reticulum

Abstract: The binding of monovanadate and decavanadate anions to sarcoplasmic reticulum vesicles was measured by equilibrium sedimentation. The affinity of vanadate binding and the molar amount of vanadium (V) bound at equilibrium is much greater with decavanadate than with monovanadate. The binding data can be rationalized in terms of one binding site per ATPase molecule for monovanadate and two sites per ATPase for decavanadate.The Ca-ATPase crystals formed with monovanadate and with decavanadate are similar in appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…32, 33 The presence of calcium or ATP in the concentrations used in the assays did not change the decavanadate rate of decomposition (data not shown). The activation energy,…”
Section: Decavanadate Stability Characterization and Interaction Witmentioning
confidence: 89%
“…32, 33 The presence of calcium or ATP in the concentrations used in the assays did not change the decavanadate rate of decomposition (data not shown). The activation energy,…”
Section: Decavanadate Stability Characterization and Interaction Witmentioning
confidence: 89%
“…In addition, extensive kinetic studies of porcine cerebral cortex Na + /K + -ATPase were undertaken to determine the nature of enzyme inhibition by V 10 . These enzymes were chosen because of their key role in normal functioning most cells of higher eukaryotic organisms (Scheiner-Bobis 2002) as well as pivotal roles in cancer cell migration (Lefranc et al 2008) and, on the other hand, known influence of V 10 on nucleotide-dependent enzymes (Boyd et al 1985;Csermely et al 1985;Varga et al 1985;Aureliano 2000;Pezza et al 2002;Aureliano and Gândara 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We have not been able to specifically determine the 'active' component but have shown that addition of V 10 does affect the activity of the phosphatase measured under specific acidic conditions using a well-established phosphatase substrate. It has long been known that decavanadate is unstable at low concentrations in aqueous solutions (Baes et al, 1976;Csermely et al, 1985;Varga et al, 1985;Chasteen, 1990;Crans et al, 2004). It is also well known that decavanadate solutions decompose at room temperature more quickly in buffer than in water Varga et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that decavanadate is unstable at low concentrations in aqueous solutions (Baes et al, 1976;Csermely et al, 1985;Varga et al, 1985;Chasteen, 1990;Crans et al, 2004). It is also well known that decavanadate solutions decompose at room temperature more quickly in buffer than in water Varga et al, 1985). Despite the fact that decomposition studies predict only mononuclear vanadium (V) as the active form of the inhibitor, there is a clear difference in our studies in the Leishmania SAP activity response to V 10 relative to VO 4 3-with the same total vanadium concentration implying that different vanadium species are involved.…”
Section: Discussionmentioning
confidence: 99%